Recovery of information through linear prediction technique in attitude estimation of spacecraft systems. (April 2015) - Khan, Naeem; Khan, Latif Ullah; Khattak, M. Irfan; Shafi, M.; Ullah, Nasim
Highlights: We have modeled spacecraft system in MRP to avoid the limitations of Quaternions. Lyapunov stability based control law is presented to stabilize nonlinear plant. Measurement loss is handled by two robust accommodating techniques. Open loop estimation is used to resolve state estimation in measurement loss case. The proposed closed loop scheme is compared with OLE to highlight the performance. Abstract: Loss of information has become a severe phenomenon in many processes including state estimation. State (attitude) estimation plays an important role in a spacecraft system. This paper proposes a novel method to determine attitude parameters based on linear prediction technique. The proposed scheme successfully recovers the lost information based on previous information samples. This scheme is compared with the standard existing technique (Open-loop Kalman filtering) thoroughly. The Normal Equation scheme has outperformed the Open-loop scheme but is computationally costly. The simulation results are deduced using a numerical nonlinear spacecraft attitude dynamic model.